Factors Affecting the Quality of Education: A Comparison Study in Vocational High School in East Java - Wulandari, Siti Sri; Trisnawati, Novi; Suratman, Bambang (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is two-fold, the first objective is to understand how to use the learning model in office administration vocational schools. In addition, this study is intended to improve the quality of education in vocational schools in Indonesia. The research was carried out at the state vocational school in the office administration department in Surabaya and Sidoarjo of East Java in Indonesia. The data were gathered through questionnaires to the respondents, while the data were analyzed using t-test. The findings showed that there were significant differences in the performance criteria and the learning model mechanism. Furthermore, there are several differences in two vocational schools including teacher education backgrounds, characteristics of students, and learning environments. The existing differences can be used to improve the quality of education, especially teacher competencies in implementing effective learning process that become a benchmark for the succeed of education.